The effect of preparation period trainings on respiratory muscle strength of hearing impaired judokas - Mayda, H. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background & Study Aim: The delay in the motor development of disabled people results from a lack of experience, rather than a loss of an ability. Thus, disabled people should be provided with suitable exercise environment, motivated to participate in physical activities and even encouraged to do sports for rehabilitation. The purpose of this study is the effect of 4-week-long preparation period judo training programs on the respiratory functions, inspiratory and expiratory muscle strength of male and female hearing impaired judokas.